Development of Salted Four-Finger Threadfin Drying Process Using a Passive Solar Drying System for Salted Four-Finger Threadfin Processing Community Enterprise, Nong Chik District, Pattani Province, Thailand - Saniso, Eleeyah; Seni, Lutfee; Hayibaka, Muhammadkhoiri; Chaydana, Huseng (Area Based Development Research Journal, 2024)
The salted four-finger threadfin processing enterprise in Nong Chik district, Pattani province of Thailand, faces challenges in producing dried salted threadfin due to reliance on open-sun drying. Each drying cycle takes 2–5 weeks and is often disrupted by dust and insects. To address these issues, this research developed a passive solar dryer in collaboration with local enterprises, educational institutions, government agencies, and the general public. The study includes: 1) an analysis of drying challenges and the design and construction of the solar dryer, 2) experimental trials using the passive solar dryer, and 3) economic and quality assessments of the salted threadfin produced. The passive solar dryer (200 x 100 x 140 cm3) maintains temperatures between 38.2–68.7°C, with an average of 54.5 ± 3.2°C, and features a solar collector panel (200 x 250 x 20 cm3) with temperatures ranging from 32.6 – 83.1°C. Each drying cycle accommodates 152 threadfins and takes nine days, increasing production capacity by 33.3% compared to open-sun drying. This innovation results in a net income increase of 90,440 Baht (around 2,650 USD) per month for the enterprise, with a payback period of two months. The quality of threadfins, in terms of color, hardness, water activity, protein content, and Staphylococcus aureus levels, is comparable to traditional methods.